Bleeding Pelvic Fracture Patients: Evolution of Resuscitation Protocols. (September 2017) - Söderlund, T.; Ketonen, T.; Handolin, L.
Background and Aims: Massive transfusion protocol seems to improve outcome in massively bleeding trauma patients, but not pelvic fracture patients. The aim of this study was to evaluate the effect of massive transfusion protocol on the mortality and fluid resuscitation of shocked pelvic fracture patients. Material and Methods: This is a trauma register study from a single hospital. From the trauma registry patients with pelvic fracture, injury severity score >15, admission base excess below −5, age >15 years, blunt trauma, and primary admission from the scene were identified. Patients were divided into two groups: Group 1—pre-massive transfusion protocol (2006–2009) and Group 2—post-massive transfusion protocol (2010–2013). Basic characteristics and intensive care unit length of stay, mortality, and fluid resuscitation data were retrieved from the registry. Standardized mortality ratio was assessed using revised injury severity classification, version II methodology. Results: Altogether, 102 patients were identified. Group 1 ( n = 56) and Group 2 ( n = 46) were comparable in their basic characteristics. The observed mortality was 35.7% and 26.1% in Groups 1 and 2, respectively. The standardized mortality ratio failed to reveal any difference between observed and expected mortality in either group. In the emergency room, the use of crystalloids decreased from 5.3 ± 3.4 to 3.3 ± 1.8 L ( p = 0.002) with increased use of fresh frozen plasma (2.9 ± 4.4 vs 5.1 ± 5.3, p = 0.007). Conclusion: No improvement in the adjusted survival of shocked pelvic fracture patients is apparent after implementation of massive transfusion protocol. Implementation of massive transfusion protocol is associated with a higher use of fresh frozen plasma and improved ratio of fresh frozen plasma:red blood cell toward the targeted 1:1 and decreased use of crystalloids.